Combination of a new ultrasonic tip with rotary systems for the preparation of flattened root canals - Medina Carita Tavares, Karina Ines [UNESP]; Pinto, Jader Camilo [UNESP]; Santos-Junior, Airton Oliveira [UNESP]; Esteves Torres, Fernanda Ferrari [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mario [UNESP] (Korean Acad Conservative Dentistry, 2021)
Objectives: This study evaluated 2 nickel-titanium rotary systems and a complementary protocol with an ultrasonic tip and a small-diameter instrument in flattened root canals. Materials and Methods: Thirty-two human maxillary second premolars with flattened canals (buccolingual diameter >= 4 times larger than the mesiodistal diameter) at 9 mm from the radiographic apex were selected. The root canals were prepared by ProDesign Logic (PDL) 30/0.01 and 30/0.05 or Hyflex EDM (HEDM) 10/0.05 and 25/0.08 (n = 16), followed by application of the Flatsonic ultrasonic tip in the cervical and middle thirds and a PDL 25/0.03 file in the apical third (FPDL). The teeth were scanned using micro-computed tomography before and after the procedures. The percentage of volume increase, debris, and uninstrumented surface area were analyzed using the Kruskal-Wallis, Dunn, Wilcoxon, analysis of variance/Tukey, and paired and unpaired t-tests (alpha = 0.05). Results: No significant difference was found in the volume increase and uninstrumented surface area between PDL and HEDM (p > 0.05). PDL had a higher percentage of debris than HEDM in the middle and apical thirds (p < 0.05). The FPDL protocol resulted in less debris and uninstrumented surface area for PDL and HEDM (p < 0.05). This protocol, with HEDM, reduced debris in the middle and apical thirds and uninstrumented surface area in the apical third (p < 0.05). Conclusions: High percentages of debris and uninstrumented surface area were observed after preparation of flattened root canals. The HEDM, Flatsonic tip, and 25/0.03 instrument protocol enhanced cleaning in flattened root canals.
Keywords: Dental pulp cavity; Root canal preparation; Ultrasonic therapy; X-ray microtomography